Care providers' experiences with and attitudes towards virtual antenatal care: Findings from a qualitative study in British Columbia. (November 2022) - Kornelsen, Jude; Nowaczek, Daria; Johnson, Robin; Mattei, Mona; Moola, Shiraz
Background: Virtual care has emerged as an adjunctive response to challenges in rural health care, including maternity care, and use has accelerated during the coronavirus disease 2019 (COVID-19) pandemic. This gives rise to the need for a strategic plan for post-COVID-19 virtual maternity care in rural communities. To date, no provincial initiative has focused on understanding and documenting the needs of maternity care practitioners to provide virtual care. Methods: Qualitative study, including virtual interviews and focus groups with rural primary maternity care providers and urban and rural specialists on perceptions of the utility of virtual maternity care pre- and post-COVID-19, and benefits and barriers of virtual care. Data were thematically analysed. Results: In total, 82 health care providers participated in the study. Health care provider responses fell into three categories: Attributes of virtual care, barriers to virtual care and system interventions needed to optimize the provision of virtual perinatal care. Participants expressed a desire for use of virtual communication tools post-COVID-19, continued ability to use fee codes for virtual care and a need for more secure texting options. The benefits of tripartite consultations were noted by many participants; impacts of the transition to virtual care included additional workload and interrupted workflow. Concerns over the lack of physical examinations and challenges in building relationships with patients when providing virtual care were frequently noted. Conclusion: Adapting the current implementation of virtual maternity care in British Columbia may be enhanced through several provider- and evidence-derived strategies, many of which are currently underway in BC. The results from this provincial survey will be used to focus further discussion on the characteristics of an optimal system to meet patient and provider needs within a rural context.